1976 El inquilinato o se vive como se puede - La Chispa (2017)
Actúan: Horacio Acosta, Shuto Díaz, Galia Kohan, Carlos Adrián Martínez, Graciela Mengarelli, Susana Rivero, Estrella Rohrstock. | Dirección Paco Giménez. | Consultado el 10 de octubre de 2016 | http://blogs.ffyh.unc.edu.ar/teatropoliticounc/la-chispa/ficha-tecnica-de-las-obras/